'n Voorgestelde raamwerk vir die skryf van 'n akademiese publikasie: voorbeelde uit die teologiese etiek - L. O. K. Lategan (Acta Theologica)
This article proposes a framework for the writing of an academic article based on a research project. References are made to theological-ethical examples. The framework outlines 12 steps for article writing. These steps are the formulation of a problem, conceptualisation, hypothesis formulation, ethical approval, methodology, philosophical framework, literature review, data capturing, analysis, validation of the hypothesis, summary and literature list. A hypothical example on abortion is used to illustrate how these steps can be employed in writing an article.